Memorandum of understanding between Universiti Teknologi MARA and University of Bangka Belitung, Indonesia / Fakulti Perakaunan - Universiti Teknologi MARA, Fakulti Perakaunan (Universiti Teknologi MARA (UiTM), 2021)
Memorandum of understanding for the promotion and collaboration on international academic and research.